1967
DOI: 10.1021/jf60153a024
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of p,p'-DDT residues in adipose and muscle tissues of beef cattle

Abstract: Two groups of beef cattle, consisting of two steers and one cow per group, received a total dose of 300 mg. of p,p'-DDT per kg. of body weight over either a 3or 30-day period. One steer from each group was sacrificed before a 7-week depletion period which followed the treatments. The remaining animals were sacrificed at the end of 7 weeks of de-pletion. Total DDT residues (DDT, DDD, and DDE) appeared on the average to be evenly dis-tributed throughout the extractable fat of beef cattle, based on samples of 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0

Year Published

1969
1969
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 7 publications
6
11
0
Order By: Relevance
“…The results are appreciably identical to those in the previous investigation (Deichmann, 1972) and support the fact that the liver is the main organ where DDT is transformed into DDD (Radomski et al, 1968;Rumsey et al, 1967;Lambert and Brodeur, 1976;Alary et al, 1971). In addition, it was also reported that DDD was detected only in the liver of laying hens after a single oral administration of p,p'-DDT (Furusawa, 2002).…”
Section: Discussionsupporting
confidence: 86%
“…The results are appreciably identical to those in the previous investigation (Deichmann, 1972) and support the fact that the liver is the main organ where DDT is transformed into DDD (Radomski et al, 1968;Rumsey et al, 1967;Lambert and Brodeur, 1976;Alary et al, 1971). In addition, it was also reported that DDD was detected only in the liver of laying hens after a single oral administration of p,p'-DDT (Furusawa, 2002).…”
Section: Discussionsupporting
confidence: 86%
“…It was reported in rats treated with DDT that DDD tended to accumulate in the liver at the same rate/level as DDT, while DDE was quantitatively of lesser amount (Mitjavila et al, 1981). The results are appreciably identical to those in the previous investigation (Deichmann, 1972) and support the fact that the liver is the main organ where DDT is transformed into DDD (Alary et al, 1971;Lambert and Brodeur, 1976;Radomski et al, 1968;Rumsey et al, 1967).…”
Section: Discussionsupporting
confidence: 82%
“…Studies along these lines have been carried out with beef cattle and dairy cows (McCulley, Villeneuve, McKinley, Phillips, and Hidiroglou 1966;Fries and Kane 1967;Rumsey, Putnam, Davis, and Corley 1967). The present trials were designed to obtain similar data for sheep.…”
Section: Nz Journal Oj Agriculturalmentioning
confidence: 99%
“…DDTt adminstered orally to cattle and sheep is partly converted to DDEt and DDDt, which accumulate with unchanged DDT in adipose tissue (Rumsey, Putnam, Davis, and Corley 1967;Fries and Kane 1967;Harrison and Mol 1968). However, domestic stock are unlikely to be exposed solely to DDT in their diet, because residues in animal feedstuffs and in farm topsoils resulting from the use of technical DDT usually comprise mixtures of the two DDT isomers together with DDE * Wallaceville Animal Research Centre, Department of Agriculture, P.B., Wellington, New Zealand.…”
Section: Introductionmentioning
confidence: 99%